Agriculture, religiosity and time: their articulation in the Mayan cosmovision - Florencia Mariani; María Victoria Rebrej Pradas (Historia y Sociedad, 2015)
The current paper analyzes the relationship among agriculture, religion and time to understand its relevance in the representation of the Mayan cosmovision. Based on the study of three different sources, we try to understand this relationship, focusing specifically on the role that corn plays in it. The analyzed sources are the Popol Vuh, the Mayan Calendar and the vase k5379. By combining these three different records we will be able to know the expression of the material and ideal reality of the Mayan society.